Introduction: The Transformation of Petitioning in the Long Nineteenth Century (1780–1914). Issue 3 (2019) - Miller, Henry
Abstract : This introductory essay, firstly, offers a comparative, historical perspective on the transformation of petitioning into a vehicle for mass popular politics across North America and Western Europe during the "long" nineteenth century (1780–1914). While petitions were well established as an instrument of state in many early modern states, from the late eighteenth century a new type of mass, public, collective petitioning, based on established or invoked rights, emerged on an unprecedented scale in many countries. Mass petitioning underpinned the nascent repertoires of collective action pioneered by social movements. At the same time, the reception of petitions was institutionalized by political authorities, particularly legislatures elected under limited suffrage, as a potential source of legitimation. Secondly, the introduction suggests why people petitioned, and continued to petition, when their campaigns were often unsuccessful in achieving immediate results. The answer lies in the manifold advantages of petitioning in enabling political organization, mobilization, identity formation, citizenship, political change, and the forming of networks with elite political actors. By shaping an emerging field examining petitioning and petitions, raising awareness of petitions as sources and the methodologies to exploit them, and addressing broad questions of interest to historians and social scientists, this special issue hopes to stimulate further research and contribute to a rich dialogue in the years to come.